Investigation on Erosion Resistance of Downhole Throttle with Ultra-high Pressure. Issue 1 (March 2020) - Ma, Huiyun; Jiang, Yuan; Yin, Qiang; Zhang, Fangfang; Chen, Shaowei; Lv, Yanxin; Lei, Guoping
Abstract: The throttling nozzle, the core element of downhole throttling tool, is seriously eroded in the producing-sand gas well. In this paper, the fixed downhole throttle developed by Petro China Southwest Oil and Gasfield Company is taken as the research object, and the flow state of gas and the movement of sand particles are expressed by RNG k – ε model and DPM model respectively. Through Fluent numerical simulation, the internal flow field distribution rule of throttle with diameter of 70mm is discussed, the most serious erosion area of throttle is obtained, and the influence of solid particle velocity, solid particle diameter and solid particle mass flow rate on the erosion of throttle are analyzed. It is meaningful to design and improve throttle according to working parameters of gas well. According to the simulation, it is believed that the fixed downhole throttle will contribute to a better understanding for erosion resistance of downhole throttle with ultra-high pressure.